Rare bird documentation form for Pine Grosbeak at Glendale Cemetery in Des Moines, 1978 - Mooney, Richard D., 1905-1997et al (1978)
Rare bird documentation form for three Pine Grosbeaks at Glendale Cemetery in Des Moines in Polk County, IA on January 24, 1978. Epson - sheet feed